Development and evaluation of a competency-based Electronic ICAO English Language Proficiency (E-IELP) platform in aviation vocational education - Laila Rochmawati; Harunur Rosyid; Delmio A. M. G. de Sousa (Jurnal Pendidikan Vokasi, 2026)
Aviation vocational education requires competency-based digital learning media that enable cadets to practice workplace communication tasks aligned with industry standards. This study developed and evaluated a web-based Electronic ICAO English Language Proficiency (E-IELP) platform to support aviation communication training for aeronautical communication cadets at an aviation vocational polytechnic in Indonesia. The platform provides ICAO-aligned learning activities, including radiotelephony read-back, situation analysis, emergency communication scenarios, and speaking tasks. This study employed a research and development (R&D) approach based on the ADDIE model, followed by a quasi-experimental pre-test–post-test control-group design to evaluate the platform's effectiveness. Forty-eight cadets participated in the study and were assigned to treatment and control groups. Data were collected through needs analysis questionnaires, curriculum analysis, expert validation forms, user response questionnaires, performance tests, and interviews. Quantitative data were analyzed using descriptive statistics, paired-samples t-tests, Welch's independent-samples t-test, and effect size estimates, while qualitative data were analyzed using thematic analysis. The platform was judged feasible by experts and received highly positive responses from users. The treatment group achieved significantly higher post-test performance than the control group, indicating that the platform effectively supports structured, repeated, and feedback-oriented aviation communication practice. However, because the study was conducted at a single institution over a four-week intervention and involved a relatively small sample using a five-point performance scale, the very large effect size should be interpreted with caution. Overall, the findings suggest that the E-IELP platform can serve as an effective supplementary competency-based digital learning platform for aviation vocational education.